The Transition Tax: Veterans of Color Learning to Navigate the Cost of Service - Will Carpenter (Adult Education Research Conference, 2025)
Veterans of color face a "transition tax" when leaving military service, experiencing significant challenges in finding employment comparable to their military roles in terms of this paper presentation will discuss how veterans of color learn to be resilient in the face of these regressive effects.
Keywords: Veteran Learning; Culture; Self-directed Learning